Odpowiedzi

2010-03-02T08:37:56+01:00
2x-3y=7 /*3
3x-5y=11 /*(-2)

6x-9y=21
-6x+10y=-22
-----------------------
y=-1

2x=7+3y
2x=7+3*(-1)
2x=7-3
2x=4 /:2
x=2

odp.
x=2
y=-1
2010-03-02T08:53:22+01:00

2×-3γ=7/-5
3×-5γ=11/3

-10×+15γ=-35
9×-15γ=33

-×=-2/-1
×=2

9×-15γ=33 podstawić pod x
9×2-15γ=33
18-15γ=33
-15γ=33-18
-15γ=15/-15
γ=-1

spr.2x-3y=7 podstawiamy pod x=2
y=-1

2×2-3×(-1)=7
4+3=7
7=7
L=P
2010-03-02T14:30:36+01:00
2x-3y=7|*3
3x-5y=11|*(-2)

6x-9y=21
-6x+10y=-22
-------------
y=-1

2x-3*(-1)=7
2x+3=7
2x=4
x=2